Symbols and Meanings of Tattoos in The Punk Community in Surakarta: Roland Barthes Semiotics Study - Panggabean, Rudolf Abigael; Miswar, Miswar; Akromullah, Hamdam; Hamzah, Hamzah; Aprisela, Jeki; Muler, Yunis (Gorga : Jurnal Seni Rupa, 2025)
This research discusses the symbols and meanings of tattoos in the punk community. Tattoos in the Punk community in Surakarta contain symbols and meanings that they want to convey to the community. This research aims to dismantle and explore the meaning contained in tattoos, highlighting the symbolic role in shaping the collective identity of the punk community of Surakarta. However, there is a negative stigma that develops in the midst of society towards a Punk community, one of which is in tattoos. So Roland Barthes's semiotic theory approach is used to prove the negative stigma about tattoos that developp in the midst of society. This research is expected to provide in-depth insight into how tattoos become an identity in the context of the punk community in Surakarta, as well as contribute to a broader understanding of the role of tattoos in responding to and representing the values of the punk subculture in the local community. This study uses a qualitative research method that is descriptive to uncover a message contained in the tattoos of the Punk community. This research found that the symbols contained in the tattoos of the Punk community such as the symbol of Anarchy, the symbol of Peace, the symbol of Equality, the symbol of Resistance, and the symbol of Antifa. Meanwhile, the meaning of tattoos based on experience is grouped into tattoos as identity, tattoos as artistic expressions, tattoos as spiritualists, tattoos as memories, tattoos as motivation, and tattoos as expressions of feelings. The negative meaning that is a stigma about tattoos that develop in society, is not something that can be proven. Rather, tattoos in the punk community are a medium to voice their anxiety about social inequality, and as a medium of individual experience.